Hormonal background of physiological aggressiveness in psychologically healthy women - Brambilla, Francesca; Speca, Azzurra; Pacchiarotti, Isabella; Biondi, Massimo (International journal of psychophysiology, 2010)
The aim of this study was to see whether or not physiological hormonal fluctuations during the menstrual cycle modulate normal aggressiveness in psychophysically healthy women. In 15 probands estrogens (E), progesterone (PROG) and free testosterone (FT) plasma levels were measured by immunochemiluminescence and levels of global aggressiveness and its subitems “verbal aggressiveness”, “suspiciousness” and “resentments” were measured by the Buss–Durkee Rating Scale in the early follicular, midluteal and premenstrual phases of the cycle. E and PROG levels varied significantly along the menstrual cycle, while those of FT, of global aggressiveness (GA) and of its subitems did not change. Values of global aggressiveness did not correlate with any of the hormonal parameters studied. However, E values correlated positively with “verbal aggression” scores in the follicular phase and positively with “resentment” in the premenstruum, while PROG levels correlated negatively with “suspiciousness” and “resentment” in the premenstrual phase of the cycle. Hormonal and psychological changes from one phase to the next (Δ) revealed that Δ E in the second half of the cycle correlated negatively with “verbal aggressiveness”, while Δ PROG from follicular to luteal and from luteal to premenstrual phases correlated negatively with “resentment”. Thus, although aggressiveness did not seem to vary along the menstrual cycle, nor to correlate with hormonal changes, hormone secretions and fluctuations might possibly modulate some of the physiological aspects of the behavioral parameter.